Assessment of quality of life in tuberculosis patients at Aland Taluk in Kalaburagi district - Babladi, Vanishree P.; Patil, Sachin; Kondaparthi, Mukteshwarachary; Salimath, Pooja V.; Biyabani, Syed A. U.; Nandyal, Bhagyashree S. (International Journal of Advances in Medicine, 2026)
Background: Tuberculosis (TB), a recalcitrant infectious disorder precipitated by Mycobacterium tuberculosis, continues to pose a formidable public health burden, exerting pervasive and long-standing detriments to health-related quality of life (HRQOL). Despite sustained implementation of national control initiatives such as the directly observed treatment, short-course (DOTS) program, TB prevalence in India remains disproportionately elevated, particularly within rural and socioeconomically marginalized populations. The disease’s multisystemic impact necessitates comprehensive evaluation beyond microbiological and clinical indices. The objective of the study was to critically appraise the quality of life among individuals diagnosed with TB in the Aland region of Kalaburagi district and to ascertain the contributory impact of structured pharmacist-led counselling on patient outcomes. Methods: A six-month prospective observational study was conducted across selected areas of Aland Taluk. Of 416 enrolled participants, 409 completed the study. Individuals aged 16–80 years were randomly assigned to intervention and control cohorts. Baseline sociodemographic characteristics and HRQOL parameters were assessed using standardized WHOQOL instruments, with follow-up evaluation performed at three months. Data were subjected to appropriate inferential statistical analysis. Results: Baseline assessment revealed a predominance of active TB cases in both cohorts. Post-intervention analysis demonstrated a substantial reduction in disease burden in the intervention group (29.61%) compared with the control group (10.34%). Significant improvements were observed across all HRQOL domains, with consistently superior outcomes in the pharmacist-intervention cohort. Conclusions: Pharmacist-mediated counselling significantly enhanced HRQOL and attenuated TB-related burden, underscoring its strategic value within integrated tuberculosis management frameworks.